God and the Anthropologist: The Ontological Turn and Human-Oriented Anthropology - Piette, Albert (Swiss Journal of Sociocultural Anthropology, 2015)
The article aims to be theoretical, and to consider the impact of the word "ontology" in anthropology. I will start from an observation of religious worship, in which at least humans, various objects and a divinity are present, as well as actions, movements, statements, perceptions and various thoughts. I shall then try to use the word "ontology" on at least two different levels: on the one hand, to describe entities, the presence of which must be assumed if the situation is to remain consistent, and on the other hand, to focus on what really exists, beyond what people do and say. Finally, I will explore the advantage of this "realist" point of view.